2021
DOI: 10.3390/ijms222011160
|View full text |Cite
|
Sign up to set email alerts
|

Protein Cargo of Salivary Small Extracellular Vesicles as Potential Functional Signature of Oral Squamous Cell Carcinoma

Abstract: The early diagnosis of oral squamous cell carcinoma (OSCC) is still an investigative challenge. Saliva has been proposed as an ideal diagnostic medium for biomarker detection by mean of liquid biopsy technique. The aim of this pilot study was to apply proteomic and bioinformatic strategies to determine the potential use of saliva small extracellular vesicles (S/SEVs) as a potential tumor biomarker source. Among the twenty-three enrolled patients, 5 were free from diseases (OSCC_FREE), 6 were with OSCC without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…With only 4 papers describing the TNM stage, most of the patients were in the late stages of OSCC (505/694; 72.8%; Seoane-Romero et al, 2012 ; Joshi et al, 2014 ; Rutkowska et al, 2020 ; Thomas et al, 2021 ). This datum confirms that more than 50% of patients with OSCC are diagnosed at an advanced stage ( La Vecchia et al, 2004 ; Goy et al, 2009 ; Gatta et al, 2015 ; Gigliotti et al, 2019 ; Fontana et al, 2021 ).…”
Section: Discussionsupporting
confidence: 77%
“…With only 4 papers describing the TNM stage, most of the patients were in the late stages of OSCC (505/694; 72.8%; Seoane-Romero et al, 2012 ; Joshi et al, 2014 ; Rutkowska et al, 2020 ; Thomas et al, 2021 ). This datum confirms that more than 50% of patients with OSCC are diagnosed at an advanced stage ( La Vecchia et al, 2004 ; Goy et al, 2009 ; Gatta et al, 2015 ; Gigliotti et al, 2019 ; Fontana et al, 2021 ).…”
Section: Discussionsupporting
confidence: 77%
“…EV-associated proteins from plasma were evaluated and revealed 43 candidate proteins with altered abundance by comparing non-cancer controls, and oral tongue squamous cell carcinoma with and without lymph node involvement [ 104 ]. Regarding saliva, Fontana et al [ 105 ] analyzed protein cargo from salivary small EVs of OSCC patients and identified differentially modulated proteins between groups. The results showed that 235 proteins were differentially modulated between OSCC-free and OSCC without lymph node metastasis (OSCC_NLNM); 157 proteins between OSCC-free and OSCC with lymph node metastasis (OSCC_LNM); 189 proteins between OSCC_NLNM and OSCC_LNM, suggesting that protein cargo from salivary EVs exhibits functional signature according to clinical conditions.…”
Section: Evsmentioning
confidence: 99%
“…Apoptotic-derived EVs or apoptotic bodies (>1000 nm in diameter) are generated from plasma membrane blebbing during cell apoptosis [ 18 , 19 , 20 ]. Exo and MVs are the main focus of the EV-based method development for several cancers, i.e., head and neck [ 16 ], brain [ 21 ], lung [ 22 ], colon [ 23 ], bladder [ 24 ], endometrial [ 25 ], ovarian [ 26 ] and prostate [ 27 ]. To the best of our knowledge, the EV-based method has never been developed for detecting the MYCN status of pediatric NB.…”
Section: Introductionmentioning
confidence: 99%